An Investigation of the Relationship Between Health Care Costs and Premiums By State - Gabriel, Shawny Jo (My University, 2015)
The focus of this project was to determine how closely related health insurance costs and premiums were across the 50 states in the 2014 Individual market. Significant changes were brought to this market in 2014 with many major elements (e.g., no gender rating, 3:1 age limit on premiums, guaranteed issue, etc.) of the Affordable Care Act finally becoming effective. While we expected to find that general cost differences among states translated directly to premium differentials, there was clear evidence suggesting otherwise. For example, the state of Minnesota had the second lowest 2014 exchange premiums while having per capita health care costs that ranked in the highest 30% of states. Using regression analysis and age/gender normalization, we examined publicly-available data to better understand the relationship of health care costs and premiums.
Color poster with text, tables, and graphs.
Keywords: Health care costs; Insurance premiums; Affordable Care Act (ACA); Posters